E-Sistus: Electronic Information System for Students with Special Needs in Supporting Inclusive School Management - Antari, Agung Dewi Megah; Agung, Anak Agung Gede; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2024)
Providing data for students with special needs is still manual, to make it easier to access the data, a digital information system needs to be developed so that its functions can be implemented more quickly. In line with these needs, this research aims to develop an e-information system for students with special needs to support inclusive school management. This research develops E-Systus development in accordance with the ADDIE development model. This research uses 4 (four) techniques in data collection, namely observation, interviews, questionnaires, and tests. This research uses qualitative descriptive analysis techniques, quantitative descriptive analysis and inferential statistical analysis. The results of this research found that the product feasibility level based on content experts obtained a percentage of 90% in the very good category. The product feasibility level based on instructional design experts obtained a percentage of 91.6% in the very good category. The level of product suitability based on media experts obtained an average value of 97.5% in the very good category. The product feasibility level based on individual trials obtained a percentage result of 94.16% which is in very good qualifications. The product feasibility level based on small group trials obtained a percentage result of 93.33% which is in very good qualifications. The Electronic Information System for Students with Special Needs (E-Sistus) has been proven to be significantly effective in supporting inclusive school management.